Cloud Security Automation Get to grips with automating your cloud security on AWS and OpenStack. - Priyam, Prashant (Packt Publishing, 2018)
In the current market, enterprise organizations are moving rapidly towards the cloud infrastructure because of its flexibility and cost effectiveness. Hence, it has become extremely important to have a security framework in place. Automating security functions will play a key role when it comes to cloud governance. This book supplies best ...